PERLINDUNGAN HUKUM TERHADAP PEKERJA RUMAH TANGGA (PRT) DALAM PERJANJIAN KERJA SECARA LISAN DENGAN PEMBERI KERJA - Herlina Intan Sari Novita (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2023)
The purpose of this study is the first to find out how legal protection is for domestic workers in verbal work agreements with employers. The second is to find out the legal consequences of having an oral work agreement between the domestic worker and the employer.Legal protection for domestic workers can only be implemented if there is a clear legal basis. However, in Regulation of the Minister of Manpower Number two Years two thousand and fifteen Article five concerning Protection of Domestic Workers there is still the word obligatory to enter into a written or oral work agreement. Meanwhile, verbal work agreements do not have strong evidence before the law. This will make domestic workers less protected for their own welfare.This type of research is a type of normative juridical research. So that the approach used is a statutory approach and a conceptual approach. Then elaborated through qualitative legal material analysis techniques by describing and analyzing in a narrative manner about an existing problem in a systematic manner.Legal protection for domestic workers in an oral work agreement with an employer has the same status as a written agreement as long as it fulfills the legal requirements of the agreement. Oral work agreements are also considered valid as long as there is no law requiring written agreements only. However, verbal work agreements also have weaknesses, especially in the certainty and submission of the parties to carry out their contents. The legal consequences of having an oral work agreement are ambiguity and disputes, difficulties in enforcing rights, exploitation risks, legal vulnerabilities, obstacles in resolving disputes, legal uncertainty, and difficulties in proving the agreements that have been made.Based on the description above, it is better if the Regulation of the Minister of Manpower Number 2 of 2015 Article 5 is revised by changing the provisions of the agreement which were originally mandatory in writing and orally to become mandatory in writing only. Because verbal work agreements do not have strong evidence before the law.Keywords: Protection, Agreement, Worker.